2009
DOI: 10.1163/156854109x422922
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline of PCR amplification from genomic extracts of DESS-preserved, slide-mounted nematodes

Abstract: Summary -Many studies use integrative methods to study both morphology and gene sequences of nematode species, yet there is little evidence to indicate the optimum criteria for merging taxonomic and molecular protocols. Preliminary evidence suggests that standard methods of desiccation and slide mounting nematode specimens in glycerin can sporadically result in degradation of genomic DNA. A time series experiment was constructed in order to assess whether this degradation of genomic DNA could be recorded and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The sample should not be stained with rose bengal; if staining is necessary, then part of the sample should be kept unstained. Given the fast denaturation of DNA in glycerin slides (Bik et al 2009), it is suggested that part of the fauna should be kept in the fixative for identification and subsequent DNA extraction procedures. …”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…The sample should not be stained with rose bengal; if staining is necessary, then part of the sample should be kept unstained. Given the fast denaturation of DNA in glycerin slides (Bik et al 2009), it is suggested that part of the fauna should be kept in the fixative for identification and subsequent DNA extraction procedures. …”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…For deep-sea nematodes, fungal sequences were most often obtained after specimens had been stored in slide mounts for long periods of time. Subsequent methodological investigations revealed that the slide mounting process can effectively degrade nematode DNA during storage [27] , allowing instead for fungal amplicons to dominate PCR reactions. Generally, if nematode DNA is well-preserved when extracted, the signal from any fungal PCR amplicons is silenced by the overwhelming majority fraction of nematode PCR amplicons during protocols for direct sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In order to corroborate that DNA remained viable in the samples stored for 2 years in DESS (as reported by Bik et al (2009) for unmounted nematodes stored for 6 months), one specimen was randomly selected to be analysed. Genomic DNA was firstly extracted from faecal samples by the NZY Tissue gDNA Isolation kit (NZYTech).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…Refrigerating or freezing samples that are combined or not with preserver solutions is also recommended for preserving samples, but is sometimes impractical under non-laboratory conditions (Kozlova et al, 2020). Other promising options are to use saturated solutions composed of dimethyl sulphoxide, disodium EDTA and saturated NaCl (hereinafter DESS), which have been successfully tested to preserve adult nematodes and their DNA for at least 1 year (Bik et al, 2009;Chałańska et al, 2016;Yoder et al, 2006). Therefore, the development and assessment of feasible preservation protocols should be promoted.…”
Section: Introductionmentioning
confidence: 99%